Good Corporate Governance, Intellectual Capital, and ICSR in Companies in Jakarta Islamic Index - Bunga Anggita Batubara; Maryam Batubara; Nur Ahmadi Bi Rahmani (Jurnal Manajemen Bisnis, 2024)
ABSTRACT Indonesia's sharia economy and finance is increasingly developing and encouragingthe birth of social responsibility based on Islamic norms called Islamic Corporate Social Responsibility (ICSR). The aim of this research is to determine the influence of good corporate governance and intellectual capital on Islamic corporate social responsibility. The GCG components used are the size of the board of directors, audit committee and independent commissioners. The type of approach in this research is quantitative. The companies in the sample are companies listed on the Jakarta Islamic Index (JII) for the 2018-2022 period using purposive sampling technique. The data analysis method used is panel data regression. The results of data testing explain that the size of the board of directors, independent commissioners, and intellectual capital have a significant positive influence on ICSR. Meanwhile, the size of the audit committee does not have a significant influence on ICSR disclosure. Simultaneously, GCG and Intellectual capital have an influence on ICSR disclosure.